Domestication and brood stock development of the orange spotted grouper, Epinephelus coioides (Hamilton, 1822) in open sea cage off Visakhapatnam coast - Xavier, Biji; Dash, Biswajit; Edward, Loveson l.; Maheswarudu, G.; Syda Rao, G. (Indian Journal of Fisheries, 2013)
Aimed at domestication and broodstock development of the orange spotted grouper (Epinephelus coioides), 63 nos. of the species of average weight 4.06 ± 0.81 kg were collected. Out of these, 54 nos. were stocked in two 6 m dia HDPE floating cages installed in Bay of Bengal off Visakhapatnam coast. Nine fishes were stocked in 5 t FRP tanks @ 1 kg per ton of water. After acclimatisation for a period of four months, 20 fishes from the cages and four fishes from the tanks were implanted with 17 α-methyl testosterone aimed at developing male brooders. The fishes were fed twice a day @ 5% body weight with Decapterus russelli, sardine and squids. Vitamin E, cod liver oil and mineral supplements were also given along with feed, twice a week. The survival rate was 100% and 94.11% in tanks and cages respectively. The final average weight of fishes at the end of the experiment was 6.99 (± 0.93) kg, registering a growth rate of 243.33 g and 206.02 g in terms of body weight per month in cages and tanks respectively. Female gonad development started four months after stocking in the cage. In one year, the mature females were cannulated and intra-ovarian egg size ranged from 400 to 600 µ. However, fishes stocked in FRP tanks did not show any sign of ovarian development till the end of the experiment. The cage reared hormone implanted fishes were oozing milt after slight pressure on abdomen whereas none of the fishes reared in tanks were found with oozing milt. The water quality parameters (ammonia and nitrite) in the tank water were significantly (p < 0.05) higher than water samples collected from the cage site. The mature females and sex reversed males from the cages were successfully induced to spawn. However, fertilized eggs were obtained only in the trial conducted in cage using hapa whereas only unfertilized eggs were obtained from the tank trial. The results of the present experiment showed that open sea floating cages are more ideal for domestication and broodstock development of the greasy grouper.